Workshop Pentingnya Pelayan Publik Yang Berintegritas Di Kelurahan Selebar - Marjoyo, Devi; Irawan, Hengki; Alidina, Alidina; Anwar, Anwar; Fajriati, Wulan Ayu (Jurnal Kewirausahaan dan Bisnis, 2021)
Improving the quality of public services is the main focus in an effort to increase community satisfaction in Selebar Village. This workshop aims to introduce the concept of integrity to public servants so that they can implement it in every interaction with the community. The importance of integrity in public services not only builds public trust but also improves the efficiency and effectiveness of services. Through this workshop, it is expected that public servants can understand the ethical and moral values that must be applied in their every action. Interactive discussions and case studies will be the main methods in delivering the material to ensure in-depth understanding. The workshop will involve representatives from various government institutions and civil society to obtain a comprehensive perspective. In addition to understanding the importance of integrity, participants will also be trained in effective communication and problem-solving skills. Practical implementation will be the main focus, with discussions on concrete steps that can be taken in everyday situations. Continuous evaluation will be conducted to measure the impact of the workshop in improving the quality of public services in Kelurahan Selebar. The conclusions of this workshop will serve as a foundation for positive change in the culture of public service delivery with integrity and orientation towards the needs of the community at the local level.